High-sensitivity Millimeter Imaging of Molecular Outflows in Nine Nearby High-mass Star-forming Regions - Liu, De-Jian; Xu, Ye; Li, Ying-Jie; Zheng, Sheng; Lu, Deng-Rong; Hao, Chao-Jie; Lin, Ze-Hao; Bian, Shuai-Bo; Liu, Li-Ming (The Astrophysical journal. Supplement series, 2021)
We present a study of molecular outflows using six molecular lines (including 12 CO/ 13 CO/C 18 O/HCO + ( J = 1−0) and CS/SiO ( J = 2−1)) toward nine nearby high-mass star-forming regions with accurate known distances. This work is based on the high-sensitivity observations obtained with the 14 m millimeter telescope of the Purple Mountain Observatory in Delingha. The detection rate of outflows (including 12 CO, 13 CO, HCO + , and CS) is 100%. However, the emission of SiO was not detected for all sources. The full line widths (Δ V ) at 3 σ above the baseline of these molecular lines have the relationship > . 12 CO and HCO + can be used to trace relatively high-velocity outflows, while 13 CO and CS can be employed to trace relatively low-velocity outflows. The dynamical timescales of the 13 CO and CS outflows are longer than those of the 12 CO and HCO + outflows. The mechanical luminosities, masses, mass-loss rates and forces of all outflows (including 12 CO, 13 CO, HCO + , and CS) are correlated with the bolometric luminosities of their central IRAS sources.